Changes in Lp-PLA2 Are Associated With Elevated Alanine Aminotransferase Levels: A Nested Case-Control Study in a Three-Year Prospective Cohort - Han, Youngmin; Yoo, Hye Jin; Kim, Yeri; Huang, Ximei; Lee, Jong Ho; Kim, Minjoo (Scripta Medica, 2023)
Background/Aim: Elevation in liver enzymes and hepatic fat may indicate a higher susceptibility to cardiovascular disease (CVD). This research sought to find anthropometric/biochemical variables significantly related to the alanine aminotransferase (ALT) increase in healthy populations.Methods: 900 healthy subjects were included in a 3-year prospective cohort study. The initial screening revealed that 538 were found to be nondiabetic (fasting glucose < 126 mg/dL) and had normal ALT levels. Among them, 79 individuals with modestly elevated ALT levels after three years were assigned to the elevated ALT group. Of the remaining 459 participants, 241 subjects matched to the increased ALT group were the control group.Results: After three years of follow-up, individuals with elevated ALT showed notably higher aspartate aminotransferase (AST), ALT, gamma-glutamyltransferase (γ-GT), high sensitivity C-reactive protein (hs-CRP), lipoprotein-associated phospholipase A2 (Lp-PLA2) activity, oxidised low-density lipoprotein (ox-LDL), urinary 8-epi-prostaglandin F2α (8-epi-PGF2α) levels and brachial-ankle pulse wave velocity (ba-PWV) in comparison to the control group. Changes (Δ) in ALT showed a positive correlation with Δ AST, Δ gamma-GT, Δ hs-CRP, Δ Lp-PLA2 activity, Δ ox-LDL, Δ urinary 8-epi-PGF2α and Δ ba-PWV. Furthermore, a direct positive link was observed between the Δ Lp-PLA2 activity and Δ AST, Δ ox-LDL and Δ ba-PWV.Conclusion: Increased Lp-PLA2 activity and other CVD risk indicators were observed to have a pronounced association with elevated ALT levels. This mild ALT elevation could potentially contribute to chronic low-grade inflammation.